Fundamental of collective bargaining in industrial relation - Ismail, Fadillah; Chan, Shiau Wei; Maulad Bahrol, Khadijah; Salleh, Siti Hasliah (Penerbit UTHM, 2020)
Bargaining plays a vital role in the economic process and it has received large attention in the economic literature. Industrial relation is a field that studies about the employment relationship which it’s an interrelation between the employer and employee or the organization and the trade union. Collective bargaining is defined as the dispute between the employer and employee where this dispute can be settled through discussion and negotiation where both parties can come to a mutual agreement and also as one decision (Edmund Heery, Nicholas Bacon, Paul Blyton & Jack Fiorito, 2010). Usually the trade union represent the employee’s interests towards the employer which the employee belongs to the trade union as well. The collective bargaining is usually about the wages scales, working hours, healthcare and safety and also training. Collective bargaining is adapt more easily when the employees demand meets the employers flexibility and easier when the firms boundary is changed accordingly. In collective bargaining wages is a topic that’s regularly being discussed or negotiated between the employer and employee (Arun, 2000; Sinha, 2000).